Impacto dos cursos MBA da FGV São Paulo na promoção e na remuneração dos profissionais - Reátegui, Vanessa Lopes Pires (2018)
The courses called MBA's in Brazil were built according to the American MBA, but with particular characteristics to the Brazilian scenario. These courses have an extensive evaluation literature, both positive about their impacts and critical evaluations of the model. However, in Brazil, there are few studies and analyzes related to this program, either in the objective aspects or in the subjective aspects. This study aimed to evaluate the impact of MBA courses, lato sensu graduate, on the remuneration and promotion of alumni graduated between 2012 and 2017, of the Getulio Vargas Foundation in São Paulo. The hypotheses tested were confirmed, since there were significant effects of 23.63% increase in the average salary of graduates in relation to their pre-MBA salary and 14.54% in the current monthly income in relation to the most probable current income of the graduates if they had not taken the MBA. A migration of lower-entry (entry level) students to higher positions (middle management) and middle management to executive level was also observed, confirming the second hypothesis of this research. From this context, the influence of the experience and the year of MBA training on current income were evaluated, and the first one impacted the income, with the result evidenced that there is a correlation between income and experience. Regarding the training time, in terms of salary differential, it was observed that there was a greater impact for those who graduated the most (2012-2015), since those graduated in the short term (2016-2017) obtained a lower salary difference significant. In the aspects related to the performance in the work, all the results were positive, having the ex-student's perception of the development of greater abilities, leadership and effectiveness of his work in relation to others without an MBA. Finally, for more than 80% of the respondents, MBA courses have a positive impact on employment, contrary to the perception about the increase in wages and / or promotion, which the majority considered not to be positive.